Acoustic Emissions of Nearly Steady and Uniform Granular Flows: A Proxy for Flow Dynamics and Velocity Fluctuations. Issue 4 (7th April 2023) - Bachelet, V.; Mangeney, A.; Toussaint, R.; de Rosny, J.; Arran, M. I.; Farin, M.; Hibert, C.
Abstract: The seismic waves emitted during granular flows are generated by different sources: high frequencies by interparticle collisions and low frequencies by global motion and large scale deformation. To unravel these different mechanisms, an experimental study has been performed on the seismic waves emitted by dry, dense, quasi‐steady granular flows. The emitted seismic waves were recorded using shock accelerometers and the flow dynamics were captured with a fast camera. The mechanical characteristics of the particle collisions were analyzed, along with the intervals between collisions and the correlations in particles' motion. The high‐frequency seismic waves (1–50 kHz) were found to originate from particle collisions and waves trapped in the flowing layer. The low‐frequency waves (20–60 Hz) were generated by particles' oscillations along their trajectories, that is, from cycles of dilation/compression during coherent shear. The profiles of granular temperature (i.e., the mean squared value of particle velocity fluctuations) and average velocity were measured and related to each other, then used in a simple steady granular flow model, in which the seismic signal consists of the variously attenuated contributions of shear‐induced Hertzian collisions throughout the flow, to predict the rate at which seismic energy was emitted. Agreement with the measured seismic power was reasonable, and scaling laws relating the seismic power, the shear strain rate and the inertial number were derived. In particular, the emitted seismic power was observed to be approximately proportional to the root mean square velocity fluctuation to the power 3.1 ± 0.9, with the latter related to the mean flow velocity. Plain Language Summary: The generation of seismic waves during granular avalanches is studied experimentally and compared to simple models. The experiments allow granular layers to reach a steady state, waves are recorded through the basement with accelerometers and grain motion is followed with a fast camera. The origin of the different frequencies of signals is discussed. The role of the particles' collisions and the attenuation of the waves in the layer is investigated. Key Points: We analyze the high‐frequency emissions and particle agitation of quasi‐steady granular flows on constant slopes Scaling laws between granular temperature, average velocity, shear rate and inertial number are derived A simple physical model for the acoustic emissions and acoustic efficiency of steady flows is developed and tested